ASSOCIATED FACTORS OF PREECLAMPSIA AMONG PREGNANT WOMEN IN KOKOP DISTRICT, BANGKALAN REGENCY - Rahmah, Azra Razita; Zainiyah, Zakkiyatus; Susanti, Eny; Wulandari, Novita; Dewangga, Angelinasyarga Sutera; Mohammad Amin (Jurnal Biometrika dan Kependudukan, 2025)
Hypertension complications associated with pregnancy affects approximately 10% of pregnancies and significantly contributes to maternal and perinatal mortality. The incidence of preeclampsia in Indonesia is considerably high, affecting 5,3% of cases per year. Preeclampsia and eclampsia rank fourth as the highest obstetric complication in East Java Province, with a percentage of around 8.11%. The frequency of preeclampsia in Bangkalan has ranked first among districts in Madura with the most cases found in Kokop District, as many as 132 cases. This study was conducted to analyze the risk factors that influence the incidence of preeclampsia in pregnant women in Kokop District, Bangkalan Regency. A cross-sectional design study was used, with chi-square test and logistic regression analysis. The sample obtained as many as 46 pregnant women who had been selected using a simple random sampling technique. Risk factors for Body Mass Index (BMI) categorized as obesity (p = 0.002; OR = 24.064; 95% CI 3.345 - 173.094) and maternal age (p = 0.009; OR = 14.321; 95% CI 1.930 - 106, 234) were considered to have the most partial in influencing the occurrence of preeclampsia in pregnant women. These two risk factors associated with preeclampsia are also influenced by the local traditions and cultural practices of the Kokop District community.